Pengaruh Edukasi dan Kemajuan Teknologi Digital terhadap Minat Generasi Z Berinvestasi di Pasar Modal Syariah (Studi Kasus Generasi Z di Kota Padang) - Fathimah Irsyad Syafar; Muhammad Rais (ARZUSIN, 2026)
The development of the Islamic capital market and the growing dominance of young investors have not been fully accompanied by increased investment interest among Generation Z, particularly in Padang City. This study aimed to analyze the effects of education and advances in digital technology on Generation Z’s interest in investing in the Islamic capital market, both partially and simultaneously. The study employed a quantitative approach with a survey design involving 100 respondents aged 17–28 years who were selected through accidental sampling. Primary data were collected using an online Likert-scale questionnaire and analyzed through multiple linear regression, t-tests, an F-test, and the coefficient of determination with the assistance of SPSS 24. The results showed that education had a positive and significant effect on investment interest, whereas advances in digital technology had no significant partial effect. Nevertheless, the model incorporating education and advances in digital technology simultaneously had a significant effect on investment interest. These findings indicate that the availability and convenience of technology are insufficient to foster investment interest without adequate understanding. This study concludes that education plays an important role in encouraging Generation Z’s interest in investing in the Islamic capital market. The results imply the need to develop investment education programs integrated with the use of digital technology to expand Generation Z’s participation in the Islamic capital market. Keywords: Investment Education; Generation Z; Investment Interest; Islamic Capital Market; Digital Technology